2019
DOI: 10.7874/jao.2019.00115
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Speech Rate and Long-Term Average Speech Spectrum between Korean Clear Speech and Conversational Speech

Abstract: Background and ObjectivesClear speech is an effective communication strategy used in difficult listening situations that draws on techniques such as accurate articulation, a slow speech rate, and the inclusion of pauses. Although too slow speech and improperly amplified spectral information can deteriorate overall speech intelligibility, certain amplitude of increments of the mid-frequency bands (1 to 3 dB) and around 50% slower speech rates of clear speech, when compared to those in conversational speech, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
(26 reference statements)
0
1
0
1
Order By: Relevance
“…Dalam pengaturan TTS menggunakan API Google TTS, kecepatan durasi dapat diatur dengan menggunakan setSpeechRate(float speechRate) [12]. Kecepatan ucap untuk berbicara dengan jelas pada laki-laki adalah 263,4 spm, sedangkan pada perempuan adalah 227,9 spm [13]. Kecepatan ucap ini akan diatur sedemikian rupa agar suara yang didengar tepat, tidak terlalu cepat dan tidak terlalu lambat.…”
Section: Api Google Ttsunclassified
“…Dalam pengaturan TTS menggunakan API Google TTS, kecepatan durasi dapat diatur dengan menggunakan setSpeechRate(float speechRate) [12]. Kecepatan ucap untuk berbicara dengan jelas pada laki-laki adalah 263,4 spm, sedangkan pada perempuan adalah 227,9 spm [13]. Kecepatan ucap ini akan diatur sedemikian rupa agar suara yang didengar tepat, tidak terlalu cepat dan tidak terlalu lambat.…”
Section: Api Google Ttsunclassified
“…There are a few studies that identify how various acoustic characteristics of Korean clear speech differ from those of conversational speech. 13,14 Similar to English clear speech, Korean clear speech is produced more slowly than conversational speech at rates as slow as 35 to 45% of the speed of conversational speech. 14 Further, Cho et al 13 demonstrated that Korean clear speech is approximately 1.4 times slower than conversational speech (syllables per second).…”
mentioning
confidence: 99%